An Analysis of Apology Strategies in Characters’ Utterances in Spider-Man Home Trilogy Movies - Harijanto, Felicia Meila; Pradipta, Bramantya (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
Abstract. This research aims to analyze the types of apology strategies and find out the most dominant type of apology strategies in Spider-Man Home Trilogy movies. Spider-Man Home Trilogy Movies consist of Spider-Man Homecoming, Spider-Man Far From Home, and Spider-Man No Way Home. This research used a descriptive qualitative method. The researcher used Ishihara and Cohen’s (2010) theory of apology strategies. The result of this research is 116 apology strategies in the Spider-Man Home Trilogy movies, which are divided into 90 An Expression of an Apology, 15 Acknowledgment of Responsibility, 5 An Explanation or Account, 4 An Offer of Repair and 2 A Promise of Non-Recurrence. An Expression of an Apology is the most dominant apology strategy in the Spider-Man Home Trilogy movies because complex relationships and conflicts between characters. The protagonist character dominates An Expression of an Apology type of apology strategy compared to the antagonist, who does not do it often. This is because the protagonist experiences complex relationships with his surroundings and conflicts with antagonists that impact his real life. To resolve the conflict, the direct apology strategy An Expression of an Apology is needed to repair the relationship. Keywords: Apology, Apology Strategies, Pragmatics, Spider-Man